Research Trends on Socio-Scientific Issues in Chemistry Learning: A Systematic Review - Dewi, Citra Ayu; Yahdi, Yahdi (FKIP Universitas Lampung, 2025)
Socio-scientific concerns have emerged as a prominent focus in contemporary chemistry education research. This study aims to analyze the trends used in socio-scientific issues in chemistry learning based on the results of research that has been carried out. This study uses a meta-analysis research design. This meta-analysis uses Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA). Data was acquired from the Scopus and Google Scholar databases utilizing scholarly publications from esteemed worldwide journals with the Scopus Q1-Q3 classification. Conduct an article search utilizing the title and keywords